Automatable splicing method for steel cord conveyor belts - evaluation of water jetting as a preparation process - Zaremba, David (Strojniški vestnik, 2017)
The increased demand of mineral resources leads to worldwide application of incessantly longer conveying systems. The length between axes can amount to 15 km and more. Owing to manageable dimensions and weight, appropriate conveyor belts are produced in segments of up to 300 m. Final assembly takes place at the conveyor system, where the multitude of segments is connected to a long conveyor belt. An important point in assembly preparation is the stripping of the steel cords, which is mainly carried out manually using rudimentary techniques. The optimization potential is high, since the adoption of automatable and application-oriented preparation methods can minimize the conveyor downtime and improve the joint quality. In this study, the application of the pure water jet is investigated, since this selective stripping method offers a lot of potential for automation and the creation of rough surfaces. The objective was to determine if an efficient, homogenous and selective removal of the rubber is possible without damaging the zinc coating of the steel cords. Following a parameter study, the generated kerf geometries and surfaces were investigated. The stripped steel cords and zinc coatings were analyzed through the preparation of micrographs. Concluding, an evaluation about the qualification of water jetting as an automatable method for joint and repair preparation is made.
Keywords: avtomatizacija; jeklena armatura; sanacija; spajanje jeklenice; transportni trak; vodni curek